Botswana Livestock Development Projects. First annual monitoring report of the First and Second Livestock Development Projects and the village Area Development Program (Nojane) - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Report on the monitoring programme in Botswana, with particular reference to the First and Second Livestock Development Projects, the Nojane ranches and the Village Area Development Programme.